Liver function following hepatitis C virus eradication by direct acting antivirals in patients with liver cirrhosis: data from the PITER cohort - Quaranta, Maria Giovanna (BMC Infect Dis, 2021)
BACKGROUND: The development of direct-acting antivirals (DAA) for HCV has revolutionized the treatment of HCV, including its treatment in patients with HIV coinfection. The aim of this study was to compare the changes in liver function between coinfected and monoinfected patients with cirrhosis who achieved HCV eradication by DAA. METHODS: Patients with pre-treatment diagnosis of HCV liver cirrhosis, consecutively enrolled in the multicenter PITER cohort, who achieved a sustained virological response 12 weeks after treatment cessation (SVR12) were analysed. Changes in Child-Pugh (C-P) class and the occurrence of a decompensating event was prospectively evaluated after the end of DAA treatment. Cox regression analysis was used to evaluate factors independently associated with changes in liver function following viral eradication. RESULTS: We evaluated 1350 patients, of whom 1242 HCV monoinfected (median follow-up 24.7, range 6.8–47.5 months after viral eradication) and 108 (8%) HCV/HIV coinfected (median follow-up 27.1, range 6.0–44.6). After adjusting for age, sex, HCV-genotype, HBsAg positivity and alcohol use, HIV was independently associated with a more advanced liver disease before treatment (C-P class B/C vs A) (OR: 3.73, 95% CI:2.00–6.98). Following HCV eradication, C-P class improved in 17/20 (85%) coinfected patients (from B to A and from C to B) and in 53/82 (64.6%) monoinfected patients (from B to A) (p = 0.08). C-P class worsened in 3/56 coinfected (5.3%) (from A to B) and in 84/1024 (8.2%) monoinfected patients (p = 0.45) (from A to B or C and from B to C). Baseline factors independently associated with C-P class worsening were male sex (HR = 2.00; 95% CI = 1.18–3.36), platelet count < 100,000/μl (HR = 1.75; 95% CI 1.08–2.85) and increased INR (HR = 2.41; 95% CI 1.51–3.84). Following viral eradication, in 7 of 15 coinfected (46.6%) and in 61 of 133 (45.8%) monoinfected patients with previous history of decompensation, a new decompensating event occurred. A first decompensating event was recorded in 4 of 93 (4.3%) coinfected and in 53 of 1109 (4.8%) monoinfected patients (p = 0.83). CONCLUSIONS: Improvement of liver function was observed following HCV eradication in the majority of patients with cirrhosis; however viral eradication did not always mean cure of liver disease in both monoinfected and coinfected patients with advanced liver disease. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1186/s12879-021-06053-3.